2020
DOI: 10.3390/ijerph17238756
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Service-Learning on PETE Students’ Effective Personality: A Mixed Methods Research

Abstract: Service-learning (SL) is a pedagogical model focused on achieving curricular goals while providing a community service. Previous research suggests that SL might promote qualities such as self-esteem, motivation, problem-focused coping, decision-making, empathy, and communication, which are associated with a psychological construct known as students’ Effective Personality (EP). These studies, however, did not specifically analyse the direct effects of SL on this construct. The aim of this study is to explicitly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…This gender difference may be related to their physical self-perception. In a recent study, boys showed better physical self-perception than girls in all subscales of physical self-perception profile and girls are at risk for their low physical self-confidence with their respective insecurity feelings and psychological disorders 24 . Social norms may also contribute to the positive correlation between BMI and SCQ scores for girls.…”
Section: Discussionmentioning
confidence: 93%
“…This gender difference may be related to their physical self-perception. In a recent study, boys showed better physical self-perception than girls in all subscales of physical self-perception profile and girls are at risk for their low physical self-confidence with their respective insecurity feelings and psychological disorders 24 . Social norms may also contribute to the positive correlation between BMI and SCQ scores for girls.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, moving now to the quantitative investigations or the quantitative part of those using mixed methods, a very recurrent research instrument was questionnaires [ 28 , 30 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The validated questionnaires used were the Entrepeneurship Competency Scale [ 51 ], the Subjective Happiness Scale [ 28 ], and the Multidimensional Attitudes Scale Toward Persons With Disabilities questionnaire [ 29 ], among others.…”
Section: Resultsmentioning
confidence: 99%
“…Intervention studies about the development of social and emotional competencies (in line with autonomous motivation using project-based learning) have reported positive changes in self-esteem, apart from better responsible decisions and higher self-awareness in primary education students [ 65 ]. A piece of research about service-learning (a pedagogical model focused on achieving curricular goals while providing a community service) showed improvements in the social self-realisation and decisive self-efficacy of Physical Education Teacher Education students, but not in self-esteem [ 66 ]. It seems that controlling interventions from teachers could develop a higher controlling motivation and a lower self-esteem in students, and further studies would be very welcome to contrast these statements.…”
Section: Discussionmentioning
confidence: 99%